واقع الصومال السیاسي في ظل الحركات الإسلامیة المعاصرة (Journal of the College of Education for Women, 2019)
Somal is considered one of the unstable and restless African Arabian country incomparison with other Arabian. It has been exposed to division and separation byEuropean colonization process that worked hardly on dividing this country according toBerlin conference (1884-1885). Even after obtaining its independence during the sixtiesand being led by civilian organizations which were unable to solve the problems ofSomalian society after obtaining the independence.Somal continued its suffering even after the military rule under the leadership ofMohammed Sayad Beree.During Beree's rule, Somal suffered from the War with Ethiopia, as well as itwitnessed an economical Crisis. It suffered also from the tribal policy through givingleadership roles to his tribal men, depriving other tribes from these roles, a matter whichled the Somalian people to end his regime and as a result to civil war that opened the doorfor political and Islamic movements. At the beginning, the Islamic movements appeared ascourts and institutions and then they united together to be Islamic courts.In addition to that, it witnessed the emergence of other Islamic parties that played agreat role in the Somalian situation because each one has its aims and wanted to apply it onSomal.Perhaps, the different aims of those movements caused this separation and divisionin Somal, a matter that has been profiteered by neighbors, especially Ethiopia whichcaused instability in the whole country.